(untitled) (Texas Journal of Medical Science, 2025)
The article discusses the clinical and pharmacological rationale for the rational use of antibacterial drugs in the treatment of infectious diseases in pediatric patients. It emphasizes the importance of individualized antibiotic therapy based on the principles of evidence-based medicine, taking into account the age-related pharmacokinetics and pharmacodynamics in children. The study highlights current challenges such as increasing antibiotic resistance, inappropriate prescribing, and lack of pediatric-specific clinical guidelines